Sifat-sifat fizik dan kandungan kimia lempung kaolin Segamat, Johor - Umar Hamzah; Khor, Kang Learn; Sahibin Rahim (Universiti Kebangsaan Malaysia, 2010)
Kaolin is a source of secondary mineral as a product of a weathering process of primary minerals. Its main component is fine grain kaolinite (<2μm) and it also contains other elements such as aluminium and iron phyllosilicate as the pigment. Aluminium rich kaolin is light in colour with high plasticity and is normally used in the ceramic, plastic, paint, paper, pesticide, pharmacology and cosmetic industries. The physical and chemical characteristics of kaolins are important for its potential application. In this study, about 25 kaolin samples were hand-augered from depths of 1-2 m at Buloh Kasap Segamat, Johor, Malaysia. Chemical analysis carried out included determination of oxides and types of minerals by X-ray diffraction and X-ray fluorescence. Shrinkage rate, rupture modulus and water absorption rate tests were carried out in the physical properties analysis. Plastic and liquid limits of the kaolin were also measured for plastic index. The Segamat kaolin was light in colour due to its high silicate composition. The highest mineral content in the kaolin was kaolinite and quartz occured as impurities. The low shrinkage rate showed that the kaolin was dense with little voids, hence very suitable for use in the ceramic industry. This kaolin has low water absorption, plasticity and durable according to the rupture modulus test.